Valuing the health states associated with breast cancer screening programmes: A systematic review of economic measures. (May 2019) - Bromley, Hannah L.; Petrie, Dennis; Mann, G.Bruce; Nickson, Carolyn; Rea, Daniel; Roberts, Tracy E.
Abstract: Policy decisions regarding breast cancer screening and treatment programmes may be misplaced unless the decision process includes the appropriate utilities and disutilities of mammography screening and its sequelae. The objectives of this study were to critically review how economic evaluations have valued the health states associated with breast cancer screening, and appraise the primary evidence informing health state utility values (cardinal measures of quality of life). A systematic review was conducted up to September 2018 of studies that elicited or used utilities relevant to mammography screening. The methods used to elicit utilities and the quality of the reported values were tabulated and analysed narratively. 40 economic evaluations of breast cancer screening programmes and 10 primary studies measuring utilities for health states associated with mammography were reviewed in full. The economic evaluations made different assumptions about the measures used, duration applied and the sequalae included in each health state. 22 evaluations referenced utilities based on assumptions or used measures that were not methodologically appropriate. There was significant heterogeneity in the utilities generated by the 10 primary studies, including the methods and population used to derive them. No study asked women to explicitly consider the risk of overdiagnosis when valuing the health states described. Utilities informing breast screening policy are restricted in their ability to reflect the full benefits and harms. Evaluating the true cost-effectiveness of breast cancer screening will remain problematic, unless the methodological challenges associated with valuing the disutilities of screening are adequately addressed. Highlights: QoL values informing breast screening policy do not fully capture benefit and harm. Undervaluation may lead to inappropriate decisions on the value of screening. The methodological challenges of valuing QoL for mammography must be addressed. Measures incorporating screening risk in the valuation process should be explored.